Expression of immune checkpoints (IDO and PD-L1) in oral tongue cancer patients: a 10-year retrospective cohort study in Pakistan - Fatima, Merium; Bashir, Shaarif; Raza, Syed Atif; Alamgeer,; Hassan, Muhammad; Abu Bakar, Muhammad; Sheikh, Ali Zafar; Tahseen, Muhammad; Sheikh, Umer Nisar; Loya, Asif; Faisal, Muhammad; Farooq, Asim; et al. (Frontiers in Oncology, 2025)
BackgroundTongue squamous cell carcinoma (TSCC) is a significant global health issue with high incidence and mortality rates. Current treatments involve surgery, radiotherapy, and chemotherapy; however, prognosis remains poor. Recent research highlights the crucial role of the tumor microenvironment, especially immune cells and checkpoints like PD-L1 and IDO, in TSCC progression.AimThis study aims to investigate the expression of IDO and PD-L1 in TSCC patients before and after chemotherapy and their association with patients’ clinicopathological characteristics.Materials and MethodsThis study involved 106 TSCC patients from Shaukat Khanum Memorial Cancer Hospital and Research Centre (SKMCH&RC) in Pakistan, with biopsies obtained from 2012 to 2022. Immunohistochemical analysis was performed on formalin-fixed, paraffin-embedded (FFPE) tumor samples to evaluate IDO and PD-L1 expression before and after chemotherapy. Data on patient demographics, tumor characteristics, and treatment were collected, and follow-up continued until January 2024.ResultsThe cohort had a mean age of 48.9 years, with a predominance of male patients. Prior to chemotherapy, 83% of patients were IDO-negative, and 75.5% were PD-L1-negative. Post-chemotherapy, IDO expression increased to 24.5% of patients (n = 26), with 84.6% exhibiting low expression and 15.4% showing high expression. While PD-L1 expression was increased to 29.2% (n = 31), with 90.3% of the positive cases showing low expression and 9.7% high expression. IDO expression was notably higher in multifocal tumors and correlated with increased comorbidities post-chemotherapy. Despite changes in marker expression, there was no significant difference in survival rates associated with IDO or PD-L1 expression.ConclusionChemotherapy appears to upregulate IDO and PD-L1 expressions in TSCC, highlighting the potential for integrating immunotherapy into treatment regimens. Further studies are needed to explore the dynamics of these biomarkers over time and their impact on patient outcomes, emphasizing the need for comprehensive therapeutic strategies.